Concussion in sports: Postconcussive activity levels, symptoms, and neurocognitive performance - Majerske, C. W.; Mihalik, J. P.; Ren, D.; Collins, M. W.; Camiolo Reddy, C.; Lovell, M. R.; Wagner, A. K. (Journal of Athletic Training, 2008)
Evidence suggests that athletes engaging in high-intensity activities after concussion have more difficulties with cognitive recovery.